Desktop Review of Ifrs Compliance, Disclosure and Relevance of Financial Statements as Perceived by Investors with Regards to their Decision Making: Array - Wadesango, Newman (Acta Universitatis Danubius. Œconomica, 2021)
The objective of financial statements as according to the Conceptual Framework is that financial statements are prepared so as to provide useful information for decision making to their users. However, there has been a growing dissatisfaction with financial statements and disclosures particularly shown by investors. The aim of this desktop research is to investigate IFRS compliance, disclosure and relevance of financial statements as perceived by investors with regards to their decision making. The research findings according to literature reviewed showed that investors still perceive financial statements to be useful and relevant in their decision making. There is need for companies to maintain credibility and reliability of financial statements and also ensuring quality disclosures so as to best provide investors with relevant information for decision making.